Activating Transcription Factor 3 as a Novel Regulator of Chemotherapy Response in Breast Cancer - Hasim, Mohamed S.; Nessim, Carolyn; Villeneuve, Patrick J.; Vanderhyden, Barbara C.; Dimitroulakos, Jim (Translational oncology, 2018)
Anthracyclines, such as doxorubicin, are used as first-line chemotherapeutics, usually in combination therapies, for the treatment of advanced breast cancer. While these drugs have been successful therapeutic options, their use is limited due to serious drug related toxicities and acquired tumor resistance. Uncovering the molecular mechanisms that mediate doxorubicin's cytotoxic effect will lead to the identification of novel more efficacious combination therapies and allow for reduced doses of doxorubicin to be administered while maintaining efficacy. In our study, we demonstrate that activating transcription factor (ATF) 3 expression was upregulated by doxorubicin treatment in a representative panel of human breast cancer cell lines MCF7 and MDA-MB-231. We have also shown that doxorubicin treatment can induce ATF3 expression in ex vivo human breast and ovarian tumor samples. The upregulation of ATF3 in the cell lines was regulated by multiple cellular mechanisms including the activation of JNK and ATM signaling pathways. Importantly, loss of ATF3 expression resulted in reduced sensitivity to doxorubicin treatment in mouse embryonic fibroblasts. Through a 1200 FDA-approved compound library screen, we identified a number of agents whose cytotoxicity is dependent on ATF3 expression that also enhanced doxorubicin induced cytotoxicity. For example, the combination of the HDAC inhibitor vorinostat or the nucleoside analogue trifluridine could synergistically enhance doxorubicin cytotoxicity in the MCF7 cell line. Synergy in cell lines with the combination of ATF3 inducers and patients with elevated basal levels of ATF3 shows enhanced response to chemotherapy. Taken together, our results demonstrate a role for ATF3 in mediating doxorubicin cytotoxicity and provide rationale for the combination of ATF3-inducing agents with doxorubicin as a novel therapeutic approach.